Blood cord’s zinc serum level is associated with general health status and outcomes: A suggestion of cut-off novelty in newborns - Andayani, Pudji; Kasab, Julia; Yunanto, Ari; Halim, Pricilia Gunawan; Marhaeni, Wulandewi; Hartoyo, Edi; Budiarto, Arief (Nurture, 2023)
Purpose: This study aims to analyze the associations of zinc serum levels in the blood cord with the general health status of neonates, along with the characteristics and outcomes in Ulin General Hospital, Banjarmasin. Design/Methodology/Approach: A cross-sectional study was conducted in October-November 2021. The subjects were divided into two groups based on the zinc serum level (≤67.5 µg/dl and >67.5 µg/dl). The cut-off was determined by the receiver operating characteristic (ROC). Findings: There were 35 subjects in the group with zinc serum level ≤67.5 µg/dl and 34 subjects in the group with zinc serum level >67.5 µg/dl. Neonates with zinc serum level over the cut-off significantly had a higher birth weight (p=0.038), lower incidence of prematurity (p=0. 02, OR 0.21; 95%CI: (0.05-0.84)), lower incidence of anemia (p=0.001, 95%CI: 0.1(0.012-.89)), neonatal jaundice (p=0.02, OR 0.3; 95%CI: 0.1-0.85), and neonatal infections (p=0.000 OR 0.008; 95%CI: 0.001-0.067). Conclusion: The zinc serum level of the blood cord is strongly associated with the general health status and outcomes of the newborn. It is also associated with the general health of neonates, birth weight, prematurity, the incidence of infection, jaundice, anemia of newborns, and the need for NICU during the treatment. Limitations: A relatively short period of observation and a small number of subjects due to the limitation of resources. Practical Implications: propose the importance of zinc intake in pregnancy as it strongly implicates the general health status and outcomes of neonates. Contribution to Literature: This study provides a cut-off value with significant results and encourages further investigation to determine the need and effects of early zinc supplementation.